African traditions in the study of religion in Africa emerging trends, indigenous spirituality and the interface with other world religions ; essays in honour of Jacob Kehinde Olupona - Adogame, Afe 1964-; Olúpǫ̀nà, Jacob Kę́hiǹdé 1951-; Chitando, Ezra; Bateye, Bolaji (Farnham [u. a.] Ashgate, 2012)
The historiography of African religions and religions in Africa presents a remarkable shift from the study of `Africa as Object` to `Africa as Subject`, thus translating the subject from obscurity into the global community of the academic study of religion. This book presents a unique multidisciplinary exploration of African traditions in the study of religion in Africa and the new African diaspora. The book is structured under three main sections - Emerging trends in the teaching of African Religions; Indigenous Thought and Spirituality; and Christianity, Hinduism and Islam. Contributors drawn from diverse African and global contexts situate current scholarly traditions of the study of African religions within the purview of academic encounter and exchanges with non-African scholars and non-African contexts. African scholars enrich the study of religions from their respective academic and methodological orientations. Jacob Kehinde Olupona stands out as a pioneer in the socio-scientific interpretation of African indigenous religion and religions in Africa. This book is to his honour and marks his immense contribution to an emerging field of study and research.
ch. 16. Folk beliefs about spiritual power and Hinduism in Ghana Albert Wuaku.
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and social problems -- Africa; Christianity and other religions -- African; Africa -- Religion -- Study and teaching -- Africa; Religious education -- Africa; Africa -- Religion -- Study and teaching; Aufsatzsammlung